2017
DOI: 10.1038/s41598-017-14335-7
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Cross-resistance and Collateral Sensitivity by Gene Expression profiles and Genomic Mutations

Abstract: In adaptive evolution, an increase in fitness to an environment is frequently accompanied by changes in fitness to other environmental conditions, called cross-resistance and sensitivity. Although the networks between fitness changes affect the course of evolution substantially, the mechanisms underlying such fitness changes are yet to be fully elucidated. Herein, we performed high-throughput laboratory evolution of Escherichia coli under various stress conditions using an automated culture system, and quantif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 45 publications
1
35
0
Order By: Relevance
“…As we mentioned aboveit can result from various mechanism of drug resistance that could be induced by the stress-response of the E. coli cell. Antibiotic-induced stress inside the bacterial cell can change the gene expression profile and it regulates the bacterial metabolism, it also has an impact on other virulence properties of bacteria [59,60].…”
Section: Antibiotics Induce Different Antibiotic Susceptibility Changesmentioning
confidence: 99%
“…As we mentioned aboveit can result from various mechanism of drug resistance that could be induced by the stress-response of the E. coli cell. Antibiotic-induced stress inside the bacterial cell can change the gene expression profile and it regulates the bacterial metabolism, it also has an impact on other virulence properties of bacteria [59,60].…”
Section: Antibiotics Induce Different Antibiotic Susceptibility Changesmentioning
confidence: 99%
“…Cell model simulations with stochastic catalytic reaction dynamics have shown that that adaptive changes in chemical concentrations after evolution are restricted to the one-dimensional subspace of chemical composition [12,13]. Furthermore, repeated bacterial evolution experiments have suggested that changes in chemical concentrations follow the same low-dimensional paths despite differences in genetic changes [14,15]. The hypothesis that evolution to increase fitness leads to this dimension reduction seen in phenotypic change explains the experimental results of common proportionality.…”
Section: Introductionmentioning
confidence: 97%
“…We consider three bacterial sequencing datasets, (1) 55 Escherichia coli ( E. coli ) MDS42 cells (Horinouchi, et al, 2017), (2) 85 Staphylococcus aureus ( S. aureus ) strains (Copin, et al, 2019), and (3) 50 Lactobacillus casei Zhang ( L. casei Zhang ) (Wang, et al, 2017). After mapping, we calculate the Spearman’s rank correlation between the RD O i and the bin’s distance to the replication origin d i .…”
Section: Resultsmentioning
confidence: 99%